MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SMP MUHAMMADIYAH 3 NGAWI - Asroriah, Fatimatul; Reynaldi, Aldi Arya Febrian (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2021)
Success in education can be measured from various aspects. Starting from the quality of students, the quality of educators, the atmosphere of the school environment, to the school administration system, and teacher professionals. However, the main factor that most influences the dynamics of education in schools is the management of the principal who is responsible for the running of an education. Based on this, the purpose of this study is to find out: 1) Principal Management at SMP Muhammadiyah 3 Ngawi, 2) Teacher professionalism at SMP Muhammadiyah 3 Ngawi, 3) Principal management in improving teacher professionalism at SMP Muhammadiyah 3 Ngawi. This study uses a descriptive qualitative approach. While the data collection techniques using interviews, observation and documentation. The data analysis process uses interactive analysis and checks the validity of the data by using observation and triangulation persistence. The results of this study were obtained, namely: (1) the principal as a leader has a fairly good ability to improve teacher professional competence, both in terms of educating and procedures for developing abilities and other matters related to education. (2) Teachers of SMP Muhammadyah 3 Ngawi are sufficient to have mature and developed personalities as seen from the success of teachers in delivering learning to students, teachers who are able to develop syllabus and learning systems, as well as monitoring and supervision on a regular and ongoing basis. (3) Principal management in improving teacher professionalism at SMP Muhammadiyah 3 Ngawi, namely: Principals provide guidance to teachers so that the quality of quality education becomes a benchmark for development in education.